Inflation and growth: New evidence from a dynamic panel threshold analysis - Stephanie Kremer; Alexander Bick; Dieter Nautz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
We introduce a dynamic panel threshold model to shed new light on the impact of inflation on long-term economic growth. The empirical analysis is based on a large panel-data set including 124 countries during the period from 1950 to 2004. For industrialized countries, our results confirm the inflation targets of about 2% set by many central banks. For non-industrialized countries, we estimate that inflation hampers growth if it exceeds 17%. Below this threshold, however, the impact of inflation on growth remains insignificant. Therefore, our results do not support growth-enhancing effects of inflation in developing countries.
Keywords: E31; C23; O40; 330; Inflation thresholds; inflation and growth; dynamic panel threshold model; Inflation; Inflationsrate; Wirtschaftswachstum; Panel; Schätzung; Welt